Antiviral drugs suppress infection of 2019‐nCoV spike pseudotyped virus by interacting with ACE2 protein. Issue 2 (10th November 2021) - Wang, Jue; Zhang, Yongjing; Hu, Shiling; Bai, Haoyun; Xue, Zhuoyin; Liu, Yanhong; Ma, Weina
Abstract: The outbreak of coronavirus disease 2019 (COVID‐19) has induced a large number of deaths worldwide. Angiotensin‐converting enzyme 2 (ACE2) is the entry receptor for the 2019 novel coronavirus (2019‐nCoV) to infect the host cells. Therefore, ACE2 may be an important target for the prevention and treatment of COVID‐19. The aim of this study was to investigate the inhibition effect of valaciclovir hydrochloride (VACV), zidovudine (ZDV), saquinavir (SQV), and efavirenz (EFV) on 2019‐nCoV infection. The results of molecule docking and surface plasmon resonance showed that VACV, ZDV, SQV, and EFV could bind to ACE2 protein, with the K D value of (4.33 ± 0.09) e −8, (6.29 ± 1.12) e −6, (2.37 ± 0.59) e −5, and (4.85 ± 1.57) e −5 M, respectively. But only ZDV and EFV prevent the 2019‐nCoV spike pseudotyped virus to enter ACE2‐HEK293T cells with an EC50 value of 4.30 ± 1.46 and 3.92 ± 1.36 μM, respectively. ZDV and EFV also have a synergistic effect on preventing entry of virus into cells. In conclusion, ZDV and EFV suppress 2019‐nCoV infection of ACE2‐HEK293T cells by interacting with ACE2.